Submission and Agency, or the Role of the Reader in the First Editions of Lewis Carroll’s Alice’s Adventures in Wonderland (1865) and Through the Looking-Glass (1871) - Virginie Iché (Cahiers Victoriens et Edouardiens)
This article analyzes the role of the reader of the first editions of Lewis Carroll’s Alice’s Adventures in Wonderland and Through the Looking-Glass. Exploring the layout of the original editions shows that, though they sometimes require the reader’s submission to their ploys, they also not infrequently empower her. The reader of the original Alice books is caught up, then, between two contradictory positions: submission and agency. This tension could be explained by the nineteenth-century shift from the early didacticism of children’s books to the modern genre of children’s literature.